AN INVESTIGATION OF THE SCATTERING OF SURFACE WAVES AT DIELECTRIC SLAB WAVEGUIDE WITH AXIAL DISCONTINUITY - Rocha, Creso S. Da (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper introduces a technique for studying the radiation due to an abrupt axial discontinuity in the geometry of a planar dielectric waveguide (Slab waveguide) when an even TM surface wave strikes the discontinuity. The mode matching technique is applied at the discontinu- ity giving rise to formally exact integral equations which are solved by the Method of Moments. [Vol. 12, No. 1 (1997), Special Issue on International Computational Electromagnetics, pp 136-141]